THE EFFECT OF CORETAX, TAX AUDITS, PENALTIES, AND AWARENESS ON INDIVIDUAL TAXPAYER COMPLIANCE AT MEDAN POLONIA - Nazla Khairina; Nurwani; Tuti Anggraini (JAT : Journal Of Accounting and Tax, 2026)
Abstract This study aims to analyze the effect of Coretax Implementation, Tax Audits, Tax Sanctions, and Tax Socialization on Individual Taxpayer Compliance at KPP Pratama Medan Polonia. The study employed a quantitative approach using primary data collected through questionnaires distributed to 125 individual taxpayers who possess a Tax Identification Number (NPWP) and have utilized the Coretax system. The sampling technique used was purposive sampling. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The outer model assessment indicated that all indicators met the required validity and reliability criteria. Furthermore, the inner model results revealed that Coretax Implementation had a positive and significant effect on Taxpayer Compliance (β = 0.224; p = 0.001), Tax Audits had a positive and significant effect (β = 0.327; p = 0.000), Tax Sanctions had a positive and significant effect (β = 0.221; p = 0.000), and Tax Socialization had a positive and significant effect (β = 0.378; p = 0.000). The Adjusted R-Square value of 0.802 indicates that the model explains 80.2% of the variance in Taxpayer Compliance. These findings suggest that optimizing Coretax implementation, strengthening tax audits, consistently enforcing tax sanctions, and enhancing tax socialization programs can significantly improve taxpayer compliance. Keywords: Coretax Implementation, Tax Audits, Tax Sanctions, Tax Socialization, Taxpayer Compliance.